2021
DOI: 10.1186/s13020-021-00441-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of TCM constitutions and neurocognitive function in elderly Macau individuals

Abstract: Background Traditional Chinese medicine (TCM) constitution contributes to predicating disease occurrence and pathological progress. In this study, we investigate the correlation between TCM constitution and neurocognitive function in elderly Macau individuals. Methods A total of 313 older adults from elderly healthcare centers were recruited at random. The data of gender, age, education, sleeping hours, physical activities were collected, and the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This project aims to systematically explore the association of cognitive impairment with SES, lifestyle, and traditional Chinese Medicine constitution in Macau elders, and to examine intestinal flora changes, biometabolic pathways, and neurological imaging and behavioral assessments. Related studies have been previously reported (Zhang Z. et al, 2021). In this study, stratified random sampling was used to obtain a representative sample based on administrative structure.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…This project aims to systematically explore the association of cognitive impairment with SES, lifestyle, and traditional Chinese Medicine constitution in Macau elders, and to examine intestinal flora changes, biometabolic pathways, and neurological imaging and behavioral assessments. Related studies have been previously reported (Zhang Z. et al, 2021). In this study, stratified random sampling was used to obtain a representative sample based on administrative structure.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Dysfunction of memory, language, reaction, and understanding are the main clinical manifestations of dementia, which is highly consistent with Qi depression in TCM ( Byers and Yaffe, 2011 ; Liu et al, 2012 ). A study ( Zhang et al, 2021 ) in Macau, including 313 elderly people (age, 77.10 ± 8.23 years), showed that Qi depression was negatively correlated with neurocognitive scores (β = −2.66, 95% CI: −4.99 to −0.33), and it was mainly manifested in affecting vision dimensions of space capability. This finding indicates that Qi depression is closely related to ARCD, which is consistent with our study’s results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have shown that traditional antidepressant prescriptions, such as Xiaoyao Powder and Chaihu Shugan Powder, could significantly increase MMSE scales and improve overall cognition ( Wu, 2015 ; Liu et al, 2018 ). This mechanism is related to increased acetyl cholinesterase (AChE) content and reduced choline acetyltransferase (ChAT) expression ( Wang et al, 2014 ), suggesting that with the development of the biological-psychological-social medical model, Qi depression caused by an accumulation of negative emotions has been proven to be closely related to the progression of cognitive decline ( Zhou et al, 2006 ; Ismail et al, 2018 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found the association of vulnerable population (Yin‐deficient constitution) with NCDs in Macao elderly individuals. 13 To further investigate how the vulnerable elders interacted with NCDs, we considered the microbiome first. The term microbiome is suggested to describe the collective genome of human body microbiota, and it can be divided into three types depending on dominant genera, named enterotypes, including enterotype 1 ( Bacteroides ), enterotype 2 ( Prevotella ) and enterotype 3 ( Ruminococcus ).…”
Section: Discussionmentioning
confidence: 99%
“…12 In our previous study on the investigation of susceptibility to NCDs in Macao elderly individuals, we recruited 400 older adults from elderly healthcare centres randomly and found that there was a vulnerable population which belonged to Yin-deficient constitution of Chinese medicine contributed to the decline of neurocognitive function, especially visual space dimension. 13 To discover the biochemical basis of the vulnerable population predisposed to NCDs for an early prediction of NCDs occurrence, multi-omics approaches, including metagenomics, metabolomic and proteomic were employed to investigate gut microbiota, faecal metabolites and urine exosomes from the elderly. In addition, follow-ups after 2 years of the vulnerable elders were conducted to assess their alteration of cognitive function level.…”
Section: Introductionmentioning
confidence: 99%